Identifying evidence-informed physical activity apps: content analysis - Kebede, Mihiretu; Steenbock, Berit; Helmer, Stefanie Maria; Sill, Janna; Möllers, Tobias; Pischke, Claudia R. (JMIR mhealth and uhealth)
Regular moderate to vigorous physical activity is essential for maintaining health and preventing the onset of chronic diseases. Both global rates of smartphone ownership and the market for physical activity and fitness apps have grown rapidly in recent years. The use of physical activity and fitness apps may assist the general population in reaching evidence-based physical activity recommendations. However, it remains unclear whether there are evidence-informed physical activity apps and whether behavior change techniques (BCTs) previously identified as effective for physical activity promotion are used in these apps. Objective: This study aimed to identify English and German evidence-informed physical activity apps and BCT employment in those apps.
Gesehen am 15.04.2020